Lost soulz [videorecording (DVD)] - Robl, Adam; Sutta, Shawn (Kino Lorber, 2024)
When aspiring rapper Sol is discovered by a group of gen-Z musicians at a party, he joins their tour through the heart of Texas and embarks on a once-in-a-lifetime adventure. Leaving behind his best friend Wesley and the surrogate family who embraced him, Sol contemplates the meaning of home. As Sol and the musicians travel across Texas, they bond over their shared pains and longings. Vibrant and bold, yet sensitive and vulnerable, these musicians pour their souls into the music they create together.